EXPERIENCE AND PROSPECTS OF MASTER’S DEGREE TRAINING OF ENGINEERING STAFF IN THE FIELD OF METALLURGICAL SCIENCE - V. M. Konstantinov (Литьë и металлургия, 2016)
The experience of training for MBA in engineering and technologies for specialties “Materials Science in Mechanical Engineering” at the department was analyzed. Efficiency of the practical-focused Master’s degree program for engineering staff of the machine-building and metallurgical enterprises was emphasized. Some ways to increase efficiency of master training of engineering experts in the field of metallurgical science and heat treatment are offered. Need of more active interaction with engineering services of the production enterprise during implementation of the master thesis was proved. Need of domination of requirements of the production enterprise is highlighted in master preparation program. The algorithm of interaction of department and technical service of the production enterprise during training of the factory expert in the correspondence practical-focused Master’s degree program is offered.